SP0087 How antigen presenting cells can be turned into tolerogenic cells. (15th June 2017) - Isaacs, JD
Abstract : Antigen presenting cells (APCs) lay at the heart of all immune responses. Whereas we generally consider APCs as cells that stimulate immune reactivity, they are also critically important for avoiding autoreactivity. Thus in health our tissues are patrolled by cells such as immature dendritic cells, which downregulate responses to self-antigens. Corruption of this process is a central factor in autoimmunity. A number of groups have developed methods to generate "tolerogenic" antigen presenting cells, that mimic the cells which regulate self-tolerance in health. It is hypothesised that administration of such cells, loaded with autoantigens, to patients with autoimmune disease should be able to overcome autoreactivity and re-establish immune regulation. Our own group has developed a therapeutic approach based upon autologous tolerogenic dendritic cells, which we derive from circulating peripheral blood monocytes. Unlike conventional mature DC, which produce IL-12p70 and other pro-inflammatory cytokines, tolDC produce no IL-12p70 but high levels of IL-10. They deviate naïve T-cells towards an IL-10-producing, anti-inflammatory phenotype and induce hyporesponsiveness in memory T-cells. In mixed cultures they dominate mature, pro-inflammatory DC and down-regulate T-cell activation. Their phenotype is stable in the presence of pro-inflammatory stimuli. Equivalent murine tolDC switch off collagen-induced arthritis, with immune deviation from IL-17 to IL-10 production by CD4+ T cells and a reduction in type II collagen-specific T cell responses. In a phase 1 trial (AuToDeCRA), we demonstrated that these cells are safe when administered into a recently inflamed target knee joint of patients with inflammatory arthritis. However, in that safety study we were unable to demonstrate a tolerogenic effect in vivo. Furthermore, we have reason to believe that administered cells may remain in the target joint, whereas a disease-modifying effect is likely to require migration to secondary lymphoid tissues. Moving forwards we are designing a study that will address the optimal administration route for tolDC, based on a technique to track the cells in vivo and to measure their effect on autoreactivity. Disclosure of Interest: None declared